PHYTOCHEMICAL PROFILING USING HIGH-RESOLUTION LIQUID CHROMATOGRAPHY-MASS SPECTROMETRY AND EVALUATION OF THE IN VITRO ANTIOXIDANT AND ANTIDIABETIC POTENTIAL OF HYDROALCOHOLIC EXTRACT OF IPOMOEA CAIRICA LEAVES - ARVIND KUMAR; MRINMOY BASAK (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objective: This paper examines the phytochemical composition and biological functions of hydroalcoholic extract of Ipomoea cairica (HEIC) leaf, which is a perennial herb traditionally used in the treatment of inflammation, diarrhea, and febrile rashes. Methods: A range of bioactive compounds was detected with the help of high-resolution liquid chromatography-mass spectrometry, among which flavonoid and alkaloid compounds, phenolic acids, and glycosides are well-known as antioxidants and antidiabetics. Results: HEIC in vitro antioxidant capacity was assessed using a series of assays, which showed that the solution has a dose-dependent radical-scavenging activity, but the activity of this compound is lower than the one of ascorbic acid. More so, the extract had moderate inhibitory effects on alpha-amylase and alpha-glucosidase enzymes with IC50 values of 130.67 μg/mL and 212 μg/mL, respectively, suggesting its possible clinical use in the control of postprandial glucose concentration. Conclusion: Major phytochemicals, including quercetin 3-rhamanoside-7-glucoside, rutin, physalis K, and 1,4-Di-O-caffeoylquinic acid, were associated with the therapeutic value of the extract. These results support conventional uses of I. cairica in herbal medicine and emphasize its potential in the preparation of natural antioxidants and antidiabetic agents.